Determinants of Female Labour Force Participation in Malaysia - Nirwana, Mohd Amin (Universiti Malaysia Sarawak, (UNIMAS), 2022)
This study aims to figure out the factors determining the participation rate of women’s labour force in Malaysia and the policies recommendation to improve their participation in the labour force. The variables used in this research including urban job opportunities, tertiary education attainment among employed person, economic growth and fertility rate. The data are ranging from the year 1990 to 2020. Using the EViews 10 software, this study tests for unit root of the data by employing the famous Augmented Dickey Fuller (ADF) test, Phillips Perron (PP) test, and Kwiatkowsky, Phillips, Schmidt and Shin (KPSS) test at level and first difference before proceeding to the cointegration analysis (Autoregressive Distributed Lag (ARDL)), ARDL error correction model, and diagnostic tests.